2001
DOI: 10.1021/jp011331g
|View full text |Cite
|
Sign up to set email alerts
|

Chlorofluoroamines: Ab Initio and DFT Studies on Their Structure, Enthalpies of Formation, and Unimolecular Reaction Pathways

Abstract: Ab initio and density functional theory calculations are reported for the chlorofluoroamines HNXY (X/Y ) F/Cl) and all possible unimolecular reaction products from their ground state. Reliable enthalpies of formation for these molecules and reaction products have been calculated using the G2 model. The large discrepancy between theory and experiment over the ∆H°f(NCl) has been resolved by reevaluating the old experimental data. Optimized structures of all the species have been obtained at various levels up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
(107 reference statements)
0
8
0
Order By: Relevance
“…Adding electron correlation at the MP2 level decreases the C−Cl distance to 2.415 Å, but the DFT calculation shows an increase to 2.599 Å. The C−Cl distance is directly related to the “looseness” of the TS and it is clear that DFT predicts a looser TS than MP2 as observed in our earlier work on HNFCl . It should be noted, however, that even for the ground state, the C−Cl distances change in a similar fashion at the three levels of theory for EC and 1,2-DCE.…”
Section: Computational Results and Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Adding electron correlation at the MP2 level decreases the C−Cl distance to 2.415 Å, but the DFT calculation shows an increase to 2.599 Å. The C−Cl distance is directly related to the “looseness” of the TS and it is clear that DFT predicts a looser TS than MP2 as observed in our earlier work on HNFCl . It should be noted, however, that even for the ground state, the C−Cl distances change in a similar fashion at the three levels of theory for EC and 1,2-DCE.…”
Section: Computational Results and Discussionmentioning
confidence: 55%
“…This influences the low-frequency normal mode vibrations (CCCl deformation and CCl stretching) for the two conformers and the TST rate constants, vide infra. Extensive searches were made for the transition state structure for HCl elimination reactions as it was felt that most of the earlier work ,, found too long a C−Cl distance for the TS. The C−Cl distance was varied from that of the reactant itself.…”
Section: Computational Results and Discussionmentioning
confidence: 99%
“…The majority were taken from standard sources, 14,22 exceptions being the enthalpies of formation for CF 3 + (+ 406 kJ mol -1 ), 23 CClF (+ 31 kJ mol -1 ), 24 SF 5 + (+ 29 kJ mol -1 ), 25 SF 5 (-915 kJ mol -1 ), 26 SF 4 (-768 kJ mol -1 ), 27 SF 2 + (+ 693 kJ mol -1 ), 27 SF 2 (-295 kJ mol -1 ), 27 SF + (+ 998 kJ mol -1 ) 27 and NCl (+ 314 kJ mol -1 ). 28 The values for the parent neutrals were taken from Manion. 29 The enthalpies of formation for the parent ions formed from trichloroethene and tetrachloroethene were taken from the photoionisation study on these molecules, 1 Tables 1−3…”
Section: Theorymentioning
confidence: 99%
“…Our earlier work on HX elimination from chlorofluoroamines also showed that MP2 level calculations overestimated barrier for HF/HCl elimination reactions in comparison with advanced level calculations. 44 In order to gain more insight into this problem, CCSD(T) calculations were carried out for HF and HCl elimination reactions from CFE and they are discussed later in this section. Moreover, experimental rate constants are compared to theoretical ones directly for CCSD(T) results in that section (III.2.D).…”
Section: Iii2b Hcl Elimination Reactionsmentioning
confidence: 99%